(Des)sentidos da loucura: experiência do sofrimento das pessoas com problemas de saúde mental em João Pessoa/PB - Araujo, Alecsonia Pereira (2022)
The socio-historical construction of madness experience is complex and crossed by multiple conceptions and interventions, which are inscribed in a stigmatizing envelope, which begins to change with the psychiatric reform movements. This doctoral thesis aimed to understand the experience of suffering of people with mental health problems, who use the Psychosocial Care Centres (CAPS) III services, in João Pessoa/PB, verifying to what extent the sociocultural changes in the forms to understand madness change the experience of human suffering and the forms of mental health care. The investigation began from three hypotheses: it was inferred that the mental health problem is incorporated in the user's life in a negative way, deteriorating their self-image and reinforcing the stigmas historically attributed to madness; the reform narrative participates and collaborates in the reconstruction of a new identity for network users, when they are recognized as subjects of rights; and that new identity and recognition have contributed to a reversal narrative of the negative self-image related to the mental health problem. In order to achieve the aims of the study, different methodologies were used, namely: field research with a qualitative approach, using the oral history research methodology, from the thematic interview, and the semi-structured interview, carried out with 22 users and 12 family members; and documental research, which supported the contextualization of the scenarios, allowing to present an overview of users. The research was carried out in 571 CAPS charts, in addition to the use of systematic observation and field diary recording. Data collection took place from 8th July 2019 until 19th March 2020 and met the assumptions of resolution 510 of 2016. The theoretical investigation allowed us to produce indications of psychosocial suffering presence, but it was only with the approximation within the research field that identified the concrete bases to verify the manifestation of suffering as psychosocial. The results suggest that the incidence of psychosocial suffering refers to the multiple expressions of the unique experience of human suffering, in its relationship with the complexity of life in its manifestations, managed and gestated in and by the intrinsic and interdependent relationship of the individual and society, that form the social totality. Documentary research already pointed to a demarcation of this relationship, especially when it allowed the elaboration of an overview of the psychosocial motivators of suffering as the first “crisis”, a scenario that was evidenced by the interviewees with the experience of suffering present in their stories of life. The analyses indicated the need for a new rationality of madness, understood as an experience of human suffering and not as a pathological experience. Therefore, it was possible to point out psychosocial suffering as a possibility of a walk, which seeks to overcome other ways of understanding human suffering beyond psychiatric diagnoses, defending approaches that recognize the human experience, hoping for a fairer society that respects the differences of its members.